2020
DOI: 10.1149/2162-8777/ab6b13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Forming Gas Furnace Annealing on the Ferroelectricity and Wake-Up Effect of Hf0.5Zr0.5O2 Thin Films

Abstract: The effect of furnace annealing on the ferroelectricity, leakage current, and wake-up effect in Hf0.5Zr0.5O2 (HZO) ultrathin film is studied as a function of furnace annealing temperature and gas environment after crystallizing the films with rapid thermal annealing in the presence of a TiN capping electrode. HZO films are deposited using atomic layer deposition in a Ge-HZO-TiN stack with Pt as the top contact electrode. The increment in the remanent polarization (Pr) is higher when the films are furnace annea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…However, TiN electrodes can act as a barrier layer to hydrogen diffusion into the ferroelectric HZO film [ 14 , 26 ]. As expected, there was no degradation in the ferroelectric properties observed in the HZO films using TiN electrodes due to FGA, which is consistent with previously reported studies [ 26 , 27 ]. In those studies, HZO films with Pt electrodes were reported to degrade ferroelectric properties during FGA due to hydrogen incorporation [ 26 ].…”
Section: Resultssupporting
confidence: 93%
“…However, TiN electrodes can act as a barrier layer to hydrogen diffusion into the ferroelectric HZO film [ 14 , 26 ]. As expected, there was no degradation in the ferroelectric properties observed in the HZO films using TiN electrodes due to FGA, which is consistent with previously reported studies [ 26 , 27 ]. In those studies, HZO films with Pt electrodes were reported to degrade ferroelectric properties during FGA due to hydrogen incorporation [ 26 ].…”
Section: Resultssupporting
confidence: 93%
“…In addition, as the annealing temperature increases, the wake-up effect is improved; notably, the sample annealed at 700 °C shows the best improvement of the wake-up effect. However, the sample annealed at 700 °C showed the lowest fatigue endurance (1.6 × 10 6 cycles), which is attributed to diffusion at the electrode interface [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shekhawat et al adjusted the annealing conditions and changed the material of BE simultaneously. [81] They added a forming gas annealing method following rapid thermal annealing with a N 2 (96%)/H 2 (4%) mixed atmosphere. The forming gas annealing process with H 2 can introduce the H element and passivate the dangling bonds, which have been proven to be harmful to conventional ferroelectric materials such as PZT.…”
Section: Optimizing Methodsmentioning
confidence: 99%